Encouraging managers of care homes for older adults to participate in research. (29th August 2019) - Smith, Nick; Towers, Ann-Marie; Collins, Grace; Palmer, Sinead; Allan, Stephen; Beecham, Jennifer
Abstract : Purpose: Research in care homes requires the co-operation of care home managers. Noting the challenges faced by the care home sector, the purpose of this paper is to consider ways in which research studies can encourage care home managers and their homes to participate in research. Design/methodology/approach: The discussion is informed by two research projects which are used to explore methods of encouraging managers of care homes to participate in research. One of the studies included interviews with care home managers to understand their reasons for taking part in research. Findings: This paper outlines and assesses three strategies for encouraging care home managers to participate in research: working in partnership, providing payment and providing personalised feedback on findings. Whereas all the strategies have the potential to encourage care home managers' participation in research, partnership working in particular was found to be fraught with difficulties. Research limitations/implications: This paper suggests that the research projects could employ any of these strategies to encourage managers of care homes to participate in research. It also suggests that proactive measures could help ameliorate the pitfalls of partnership working. Originality/value: This paper shows the advantages and disadvantages of using a combination of strategies for encouraging the participation of care home managers in research.